Vaccine antigen-based genotyping of Bordetella pertussis by direct Sanger sequencing of clinical samples in Peru from 2018 to 2019 - Eduardo Juscamayta-López; Betsabé Vega-Abad; Faviola Valdivia; María Pía Soto; Helen Horna; Ruth García-de-la-Guarda (Microbiology Spectrum)
ABSTRACT Despite widespread vaccination, pertussis (caused by Bordetella pertussis) persists in many countries, frequently causing outbreaks and severe cases in infants. The resurgence of pertussis may be due to genetic changes in the vaccine antigens of circulating B. pertussis strains. However, current typing methods, which depend on bacterial cultures, hinder our understanding of B. pertussis genotypes, especially in developing countries. This study aimed to analyze vaccine antigen-based genotypic variants (ptxP, ptxA, fim3, and prn) of B. pertussis in Peru from 2018 to 2019 via direct Sanger sequencing of nasopharyngeal swabs (n = 96). PCR-based sequencing was successful for the genes ptxP in 86% (83/96), ptxA in 100% (96/96), fim3 in 75% (72/96), and prn in 68% (65/96) of the samples. The ptxP3 variant was found in 100% (83/83), ptxA1 in 100% (96/96), fim3-1 in 97.3% (70/72), fim3-2 in 2.7% (2/72), and prn2 in 100% (65/65) of the samples. Sixty-three samples yielded a complete allelic profile, with genotype VI (ptxP3-ptxA1-fim3-1-prn2) predominating nationwide (96.8%), mainly in Lima (29.5%), Amazonas (13.1%), Callao (11.5%), and La Libertad (11.5%). Genotype VII (ptxP3-ptxA1-fim3-2-prn2) was less common (3.2%), found in Lima (50%) and Callao (50%). The predominance and expansion of genotype VI suggested the presence of biological traits linked to infection, possibly due to the ptxP3 allele, such as high respiratory colonization or increased pertussis toxin production, which could potentially increase disease transmission and severity. These findings will facilitate Peru’s ability to monitor and control B. pertussis, improving public health responses and reducing the outbreak incidence and severity.IMPORTANCEDespite widespread vaccination, pertussis (caused by Bordetella pertussis) still causes severe outbreaks in infants worldwide. Genetic changes in the vaccine antigens of B. pertussis strains may drive this resurgence. Current culture-based typing methods limit our understanding of these genotypes, particularly in developing countries. This study provides valuable insights into the genotypic variability of B. pertussis in Peru from 2018 to 2019, employing an isolation-free genotyping method allowing the direct Sanger sequencing of vaccine antigen genes from clinical samples. These findings can enhance public health decision-making by improving our understanding of the genetic changes that drive severe pertussis outbreaks, particularly in developing countries that use whole-cell vaccines. This knowledge enables rapid outbreak responses, improved vaccine strategies, and strengthened surveillance, prevention, and control measures.